Aprimoramento da sistemática U-Pb através do método de traços de fissão e técnicas de caracterização: termocronologia da faixa Brasília e sua correlação com a bacia do Paraná - Resende, Rosana Silveira [UNESP] (2015)
Fission-Track (FT) Method is widely used to obtain apparent age and thermal histories related to intermediate to low temperature thermotectonic events (below 400ºC for zircon) commonly undetectable by other dating methods. The FT age refers to the cooling age within the partial annealing zone (PAZ), while the U-Pb age is related to the mineral formation time - crystallization or recrystallization age - and sometimes can indicate the occurrence of high grade metamorphic events. The use of both methods enables a more comprehensive geochronological study of orogenic sources and sedimentary basins. This paper aims to provide new information about cooling ages related to possible orogenic sources located in the southern portion of the Brasília Belt, which probable provided detrital sediments to the Paraná Basin. The work was conducted in metasedimentary rocks of the southern segment of the Brasília Belt sedimentary rocks of the Paraná Basin which currently arise on the surface. Other purpose of this paper is to investigate the effect of the chemical etching - used to reveal fission tracks - in the lattice, chemical composition, morphology and isotope geochemistry of zircon grains. The obtained results from the FT ages clearly show the metamorphic intensity direction associated within the Brasília Belt, i.e., decreasing towards São Francisco-Congo Craton. While U-Pb ages, distributed in the range from 1.6 to 3.2 Ga, show that the metamorphic temperature associated associated to metasedimentary rocks did not exceed 900ºC. Regarding to U-Pb ages obtained in the Paraná Basin is inferred as possible sources those formed during the orogenic cycles: Famatinian; Gondwanide; Brazilian (I,II,III); Tonian (Lower Neoproteroic); Stenian (Mesoproterozoic); Statherian, Orosirian and Rhyacian (Paleoproterozoic). Among which stand out the Tocantins Province, São Francisco-Congo Cratoon, Mantiqueira System and terranes related to the western margin of the...